Inclusive Early Childhood Education for Children With and Without Autism: Progress, Barriers, and Future Directions - Siller, Michael; Morgan, Lindee; Wedderburn, Quentin; Fuhrmeister, Sally; Rudrabhatla, Asha (Frontiers in Psychiatry, 2021)
University-affiliated lab and model schools play an important role in creating educational innovations in inclusive early childhood education (ECE) for young children with Autism Spectrum Disorder (ASD). In the United States, access to inclusive high-quality ECE programs for young children with disabilities has been required by law for over 40 years, has been recommended by leading professional organizations, and has been emphasized in federal public policy initiatives. Yet, improvement in the rates of young children with disabilities experiencing inclusion has been limited. This review article consists of three parts. First, we identify and describe four barriers to wide-scale implementation of inclusive ECE programs for children with ASD in the US. These barriers include (1) the fragmented nature of the ECE system in the United States, (2) the age at which ASD is typically first diagnosed in the community, (3) the diverse presentation/support needs of children with ASD, and (4) the thoughts and feelings of parents of children without disability about inclusion. Second, we used a snowball sampling approach to identify nine leading university-affiliated, inclusive lab and model schools for young children with ASD. By describing these programs, we highlight similarities and differences between programs, and capture the unique ways in which these programs adapt to local conditions, resources, and barriers (e.g., federal and state regulations, funding sources, community resources, institutional structures and priorities, professional orientation and training, access to families and staff). Finally, we propose a roadmap for researchers focused on the development, evaluation, and implementation of community-viable inclusive ECE programs in ASD. This roadmap leverages synergies between inclusive university-affiliated lab and model preschools in ASD, and proposes the formation of a research network that creates an infrastructure for cross-program collaboration.